Implementing Campus Greening Initiatives : Approaches, Methods and Perspectives - Leal Filho, Walter; Muthu, Nandhivarman; Edwin, Golda; Sima, Mihaela (World Sustainability Series, 2015)
Firmly rooted in the theory and practice of sustainable development, this book offers a comprehensive resource on sustainability, focusing on both industrialized and developing nations. Implementing Campus Greening Initiatives: Approaches, Methods and Perspectives is an attempt to promote and disseminate the work being done in this field by universities around the world. The need to integrate the principles and concepts of green campuses and sustainability into the core of students' educational experiences, from high school to college or university, has now been broadly recognized. By doing so, we can ensure that the students of today and tomorrow will acquire the knowledge, skills, attitudes and values needed to create a more sustainable economy and social environment.